STUDI EFISIENSI PASAR MODAL INDONESIA BENTUK SETENGAH KUAT PADA MASA PANDEMI COVID-19 (Perusahaan Transportasi Di Bursa Efek Indonesia Tahun 2019-2020) - Muhammad Tharmizi Junaid Tharmizi; Muh. Irfandy Azis; Ahmad Juliana; Jescynia Marchella Lahengke; Aan Digita Malik (Politeknik Caltex Riau, 2021)
This research aims to determine how the transportation industry in Indonesia fared during the COVID-19 pandemic. Is this segment of the Indonesian capital market semi-efficient during the COVID-19 pandemic? In order to measure the sample size, Purposive Sampling and Market Adjusted Model approaches are used. The data used is abnormal return data for all IATA-listed transportation providers there are 35 firms that will be evaluated on the Indonesia Stock Exchange in the 2019-2020 term. The Abnormal Return, Market Reaction Speed, Normality Test, and Independent Different Test were used to examine the data (Independent Sample T-Test). The findings of this research show that transportation companies listed on the Indonesia Stock Exchange are semi-strongly efficient. Prices were altered by the news of the COVID-19 pandemic with atypical returns that did not last long, allowing the market to achieve a new price equilibrium point. There were also considerable discrepancies in the results of the several abnormal return tests before and after the COVID-19 pandemic. Keywords: efficient market hypothesis, semi-strong, event study, abnormal return